2022
DOI: 10.1089/pop.2021.0306
|View full text |Cite
|
Sign up to set email alerts
|

A Missed Opportunity? How Health Care Organizations Engage Primary Care Clinicians in Formal Social Care Efforts

Abstract: Health care organizations increasingly recognize the impact of social needs on health outcomes. As organizations develop and scale efforts to address social needs, little is known about the optimal role for clinicians in providing social care. In this study, the authors aimed to understand how health care organizations involve clinicians in formal social care efforts. In 2019, the authors conducted 33 semi-structured interviews with administrators at 29 health care organizations. Interviews focused on the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In April–July of 2019, we conducted 33 semi-structured interviews with administrators at 29 health care organizations. 6 , 12 , 13 , 20 All interviewed organizations had already established programs to identify and address patients’ social needs, such as food, housing, transportation, utilities, or other needs related to economic insecurity. The local Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In April–July of 2019, we conducted 33 semi-structured interviews with administrators at 29 health care organizations. 6 , 12 , 13 , 20 All interviewed organizations had already established programs to identify and address patients’ social needs, such as food, housing, transportation, utilities, or other needs related to economic insecurity. The local Institutional Review Board approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…Additional details on the study sample and interview methodology can be found in prior publications. 6 , 12 , 13 , 20 …”
Section: Methodsmentioning
confidence: 99%